Influence of orifice in entropy generation and exergy analysis under transient condition for large diameter natural circulation loops. (29th October 2021) - Elton, D.N.; Arunachala, U.C.; Rajat, A.C.
Stable power generation is of concern due to instability in NCL. The entropy generation analysis in a 38.89 mm diameter loop identified the flow reversals by a drop in its value after a peak. Orifice plates and operating procedures lead to a change in threshold value. During unsteady state, the least entropy generation was observed with β = 0.77. At higher power, constant power generation is possible with low orifice as it exhibits better exergy efficiency. The entropy generated due to friction was negligible compared to that by heat transfer.